Estimation of absolute renal uptake with technetium-99m dimercaptosuccinic acid: direct comparison with the radioactivity of nephrectomy specimens - Lima, Mariana da Cunha Lopes de (2008)
CONTEXT AND OBJECTIVE: Studies using radionuclides are the most appropriate method for estimating renal function. Dimercaptosuccinic acid chelate labeled with technetium-99m (99mTcDMSA) is the radiopharmaceutical of choice for high-resolution imaging of the renal cortex and estimation of the functional renal mass. The aim of this study was to evaluate a simplifi ed method for determining the absolute renal uptake (ARU) of 99mTc-DMSA prior to nephrectomy, using the radioactivity counts of nephrectomy specimens as the gold standard. DESIGN AND SETTING: Prospective study at the Division of Nuclear Medicine, Department of Radiology, Universidade Estadual de Campinas. METHODS: Seventeen patients (12 females; range 22-82 years old; mean age 50.8 years old) underwent nephrectomy for various reasons. Renal scintigraphy was performed three to four hours after intravenous administration of a mean dose of 188.7 MBq (5.1 mCi) of 99mTc-DMSA, which was done six to 24 hours before surgery. The in vivo renal uptake of 99mTc-DMSA was determined using the radioactivity of the syringe before the injection (measured using a dose calibrator) and the images of the syringe and kidneys, obtained from a scintillation camera. After surgery, the reference value for renal uptake of 99mTc-DMSA was determined by measuring the radioactivity of the nephrectomy specimen using the same dose calibrator. RESULTS: The ARU measurements were very similar to those obtained using the reference method, as determined by linear regression (r-squared = 0.96). CONCLUSION: ARU estimation using the proposed method before nephrectomy seems to be accurate and feasible for routine use.